Smart Village: A Means of Empowering the Krisik Village Community through an Intelligent Information System Based on Online Administration Service Solutions - Muhammad Teguh Prayoga; Ani Budi Astuti; Gusti Ayu Putu Rawi Rotchildi; Olyvia Maria Kalangi; Muhammad Ariq Deriz Putra; Muhammad Ibnu (Journal of Innovation and Applied Technology, 2023)
Administration is a fundamental need of society. The implementation is still not practical and simple results in a domino effect that can have an impact on other sectors such as the economy. The demographic condition of Krisik Village shows that time inefficiency will result in a lot of losses. Moreover, the absorption of existing village funds shows that the use of paper for administration is still very large which is not in accordance with the 13th point of the Sustainable Development Goals, coupled with the COVID-19 pandemic which has exacerbated the situation with the imposition of various restrictions on sectors in society. Krisik Village needs a solution to facilitate the administrative process in terms of distribution delivery and management in order to create a flexible and efficient system. Thus Smart Village, an application that can accommodate administrative processes at the village level using the Android system, become a solution.